2015
DOI: 10.18632/oncotarget.3795
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of thioredoxin 1 leads to apoptosis in drug-resistant multiple myeloma

Abstract: Multiple myeloma (MM) is a hematological malignancy characterized by the aberrant accumulation of clonal plasma cells in the bone marrow. Despite recent advancement in anti-myeloma treatment, MM remains an incurable disease. This study showed higher intrinsic oxidative stress and higher Trx1 and TrxR1 protein levels in MM cells compared to normal cells. Drug-induced Trx1 (PX-12) and TrxR1 (Auranofin) inhibition disrupted redox homeostasis resulting in ROS-induced apoptosis in MM cells and a reduction in clonog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 61 publications
5
92
0
Order By: Relevance
“…Our findings complement other studies that showed that modulation of antioxidant systems, glutathione and CuZnSOD, abrogates bortezomib resistance and resensitizes resistant myeloma cells to bortezomib. 15,35 Interestingly, despite higher Trx1 protein levels in bortezomib-resistant myeloma cells, 14 its inhibition using either a specific inhibitor PX-12 or Trx1 anti-sense plasmid did not sensitize bortezomibresistant U266 cells to bortezomib (data not shown). However, the underlying mechanism for this effect remains to be elucidated.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our findings complement other studies that showed that modulation of antioxidant systems, glutathione and CuZnSOD, abrogates bortezomib resistance and resensitizes resistant myeloma cells to bortezomib. 15,35 Interestingly, despite higher Trx1 protein levels in bortezomib-resistant myeloma cells, 14 its inhibition using either a specific inhibitor PX-12 or Trx1 anti-sense plasmid did not sensitize bortezomibresistant U266 cells to bortezomib (data not shown). However, the underlying mechanism for this effect remains to be elucidated.…”
Section: Discussionmentioning
confidence: 93%
“…14 Caspase-3 and 9 activity assays Caspase-3 activity was determined in treated and untreated myeloma cells by using Ac-DEVD-AMC (Enzo Life Sciences, http://www.enzolifesciences.com/ALX-260-031), a caspase-3 substrate, as described previously.…”
Section: Cell Viability Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase-3 activity assay 0.5 Â 10 6 cells were treated with the appropriate drugs for indicated period of time in 24-wells plate. Caspase-3 activity within the treated and untreated myeloma cell lines and PBMCs was determined as described previously following the cleavage of Ac-DEVD-AMC (Enzo Life Sciences, NY, USA), a caspase-3 substrate [26]. Briefly, treated or untreated cells (0.5 Â 10 6 cells) were pelleted, washed with PBS, re-suspended in 10-15 ml of PBS, and transferred to black-walled 96-wells plate.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…A dicholorofluorescein (DCF) assay was used to determine cellular ROS generation in myeloma cells and control PBMCs as described previously [26]. Briefly, 1 Â 10 6 of treated or untreated cells were washed with PBS and incubated with 10 mM H 2 DCFDA (Molecular probes, CA, USA), a redox sensitive cell permeable dye, for 15 min.…”
Section: Measurement Of Intracellular Ros Generationmentioning
confidence: 99%